Key informants for peadiatric eye disease case finding in Madagascar - Chimeziri, Anderson (Department of Public Health and Family Medicine, 2020)
As at 2014, 19 million children aged < 16 years were visually impaired, 1.4 million of these children were blind and needed visual rehabilitation interventions. Surveys, mostly utilizing key informants (KI), have suggested that the prevalence of blindness in children in Sub Saharan Africa ranges between 2 -8 per 10,000 children. Childhood eye disease is rare and conditions are difficult to detect; thus, surveys to estimate the prevalence of blindness requires rigorous, costly and difficult methods to obtain reasonable estimates among children. Key informant programs, which engage the community in case finding, have been shown to be a reasonable alternative to large scale surveys and were used in Madagascar in 2014 by four regional eye care programmes. I propose to analyse the data generated from the programmes to quantify the prevalence of eye conditions among children and how the KIs performed. Method: The analysis will use data collected in a cross sectional approach. Statistical analysis will be conducted using Stata (15.0) statistical software. Data from all of the KI registers will be pooled and overall magnitude estimates calculated. KI productivity and sub-group analyses will include assessment of demographic characteristics of the children and the KI by age and sex. Ethical approval will be provided by the UCT Health Research and Ethics Committee and the Madagascar Ministry of Health. Discussion: The results from this study will help child eye health programmes to determine how best to use KI to better serve children with vision loss, and guide in the provision of eye services for children care.